Analysis and Application of Transition Systems Based on Petri Nets and Relation Matrices to Business Process Management. (31st March 2020) - Han, Dong; Tian, Yinhua
Abstract : In order to improve the efficiency of conformance checking in business process management, a business alignment approach is presented based on transition systems between relation matrices and Petri nets. Firstly, a log-based relation matrix of the events is obtained according to the event log. Then, the events in the relation matrix are observed and the transitions in the model are firing, and the activities in the log and in the model are compared. Next, the states of the log and the model are recorded until no new state can be generated, so a transition system can be obtained which includes optimal alignments between the event log and the process model. Finally, two detailed algorithms are presented to obtain an optimal alignment and all optimal alignments between the trace and the model based on the given cost function, respectively. The availability and effectiveness of the proposed approach are proved theoretically.